2017
DOI: 10.1089/neu.2016.4415
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Blunt Cerebrovascular Injury in Pediatric Trauma: Validation of the “Utah Score”

Abstract: Risk factors for blunt cerebrovascular injury (BCVI) may differ between children and adults, suggesting that children at low risk for BCVI after trauma receive unnecessary computed tomography angiography (CTA) and high-dose radiation. We previously developed a score for predicting pediatric BCVI based on retrospective cohort analysis. Our objective is to externally validate this prediction score with a retrospective multi-institutional cohort. We included patients who underwent CTA for traumatic cranial injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…The new McGovern score (Table 1) assigned 2 points to patients involved in a motor vehicle accident or automobile-pedestrian accident and redefined "high-risk" patients as those patients who had a McGovern score ≥ 3. A dichotomized score was kept as suggested in the study conducted by Ravindra et al 41 to facilitate easy clinical decision making regarding whether angiography was necessary. A logistic regression model was made for the McGovern risk categorization and its association with BCVI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new McGovern score (Table 1) assigned 2 points to patients involved in a motor vehicle accident or automobile-pedestrian accident and redefined "high-risk" patients as those patients who had a McGovern score ≥ 3. A dichotomized score was kept as suggested in the study conducted by Ravindra et al 41 to facilitate easy clinical decision making regarding whether angiography was necessary. A logistic regression model was made for the McGovern risk categorization and its association with BCVI.…”
Section: Discussionmentioning
confidence: 99%
“…They reported demographic, clinical, and imaging characteristics in a cohort of pediatric patients diagnosed with BCVI to identify variables that could be used to determine which pediatric trauma patients are at a higher risk for developing BCVI. 41,42 Additionally, these authors proposed a screening tool based on clinical evaluations and CT imaging to identify which patients who present to the emergency department with blunt trauma should undergo angiography in order to make a definitive diagnosis of BCVI. Although this score was validated in pooled data from other centers (Monroe Carell Children's Hospital, Nashville, Tennessee; St. Louis Children's Hospital, St. Louis, Missouri; Texas Children's Hospital, Houston, Texas), the sensitivity remained low at 59%, thereby indicating the questionable utility of this score as an initial screening tool.…”
mentioning
confidence: 99%
“…A recent multicenter validation study of the Utah Score also showed that compared with the Denver Criteria, the Utah Score correlated better with the risk of BCVI in the pediatric population and the Denver Criteria would have led to overscreening and unnecessary radiation exposure. 40 The initial study showed that a score of Յ2 had a 7.9% 22 risk of BCVI, whereas the validation study showed an even lower number of 2.7% 40 BCVI risk. A score of Ն3 had a BCVI risk of 39.3% per the initial study 22 and 18.1% per the validation study.…”
Section: Bcvi In the Pediatric Populationmentioning
confidence: 99%
“…Many screening criteria have been proposed to identify patients at risk of BCVI. Initial studies on BCVI were performed at the Denver Health Medical Center and the University of Tennessee Health Science Center, and the criteria proposed by them were named the Denver Criteria 31,35 and the Memphis Cri- a Score Յ2 ϭ low risk (7.9% risk per initial study 22 and 2.7% per validation study 40 ). Score Ն3 ϭ high risk (score of 3 had a 39.3% risk of BCVI per initial study 22 and 18.1% risk per validation study 40 ).…”
Section: Bcvi Screeningmentioning
confidence: 99%
See 1 more Smart Citation